Little Feet (Part II) - Budan, Bai (Budan, Bai, 2005)
Verzio FF Submission Bai Danu, foot-bound since she was seven years old, and Liu Buhan got married over forty years ago after their spouses died, bringing together each other’s children (Mrs. Bai¡’s two sons and daughter and Mr. Liu¡’s three daughters) into one family. Their children have now become grandparents, but are no longer at their parents’ side, and all have differences of opinion on how to take care of their parents in their old age. So, even though the couple are already in their eighties, they still have to get up early to work in the fields, coming back home late in the evenings. Because of her bound feet, Bai Danu is forced to hobble along in the rain with the help of her two walking sticks, and sit down when working in the fields.